Prognostic factors associated with six month mortality of critically ill elderly patients admitted to the intensive care unit with severe acute cholangitis. Issue 3 (March 2021) - Novy, Emmanuel; Carrara, Lucie; Remen, Thomas; Chevaux, Jean-Baptiste; Losser, Marie-Reine; Louis, Guillaume; Guerci, Philippe
Abstract: Background: Little is known about the outcomes of elderly patients admitted to the intensive care unit (ICU) with severe acute cholangitis (SAC). The objectives were to describe the 6-month mortality in patients with SAC ≥75 years and to identify factors associated with this mortality. Methods: Bi-center retrospective study of critically ill elderly patients with SAC conducted between 2013 and 2017. Demographic and clinical variables of ICU and hospital stays with a 6-month follow-up were analyzed. Results: 85 patients, with a median [Q1–Q3] age of 83 [80–89] years were enrolled of whom 51 (60%) were men. SAC was due to choledocholithiasis in 72 (85%) patients. Median [Q1–Q3] ICU length of stay was 3 [2–6] days. Median [Q1–Q3] admission SAPS II was 50 [42–70]. The ICU and 6-month mortality rates were 18% and 48% respectively. Multivariate analysis showed that malnutrition (OR = 34.5, 95% CI [1.4–817.9]) and a decrease in SOFA score at 48 h (OR by unit 0.7, 95% CI [0.5–0.9]) were associated with higher 6-month mortality. Conclusion: In their decision-making process, ICU physicians and hepato-pancreato-biliary surgeons could use these data to estimate the probability of survival of an elderly patient presenting with SAC and to offer time-limited trials of intensive care. Trial registration: NCT03831529.